2019
DOI: 10.1111/jcmm.14810
|View full text |Cite
|
Sign up to set email alerts
|

TPD7 inhibits the growth of cutaneous T cell lymphoma H9 cell through regulating IL‐2R signalling pathway

Abstract: IL‐2R pathway is a key regulator in the development of immune cells and has emerged as a promising drug target in cancer treatment, but there is a scarcity of related inhibitors. TPD7 is a novel biphenyl urea taspine derivate, which has been shown anti‐cancer effect. Here, we demonstrated the anti‐cancer activity of TPD7 in cutaneous T cell lymphoma and investigated the underlying mechanism of TPD7 through IL‐2R signalling. The inhibitory effect of TPD7 on cell viability exhibited a strong correlation with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(80 reference statements)
1
1
0
Order By: Relevance
“…Findings have shown that BCR-ABL exerts anti-apoptotic effects that play an important role in the development of CML (20). Furthermore, the intrinsic mitochondrial pathway is one of the two main apoptotic pathways (21). In the current study, ND-09 was found to induce apoptosis in K562 cells, an effect that was relatively higher in K562 cells than in JURKAT and HUT78 cells (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Findings have shown that BCR-ABL exerts anti-apoptotic effects that play an important role in the development of CML (20). Furthermore, the intrinsic mitochondrial pathway is one of the two main apoptotic pathways (21). In the current study, ND-09 was found to induce apoptosis in K562 cells, an effect that was relatively higher in K562 cells than in JURKAT and HUT78 cells (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Besides, a vitamin A derivative, 9-cis-RA, induced CTCL cellular apoptosis dose-and time-dependently via decreasing JAK1/STAT3/STAT5 phosphorylation, Bcl-xL and cyclin D1 levels [114]. A novel taspine derivate TPD7 was able to bind to the IL-2 receptor in CTCL and therefore suppressed the downstream cascade, including JAK/STAT and PI3K/AKT/mTOR [115] Additionally, another compound ONC201 exerted time-dependent cell survival inhibition in CTCL cell lines and patient-derived primary CD4+ malignant T cells, and the JAK/STAT pathway was downregulated with ONC201 treatment [116]. These derivatives or inhibitors demonstrated effectiveness and selectivity in harnessing JAK/STAT in order to treat CTCL.…”
Section: Monotherapymentioning
confidence: 99%